Public responses towards subsidies reduction in major towns of Sarawak / Chris Herbert Isik and Rhohanniza Amika@Ammega - Isik, Chris Herbert; Amika@Ammega, Rhohanniza (2011)
The reduction of subsidies has increased the price of goods and services. Therefore, it has also contributed to the increased amount of money being spent by the public. The study is to examine the general public responses towards government decision to reduce subsidies. Random samples of 400 questionnaires were given to the general public from four major towns in Sarawak mainly Kuching, Sibu, Bintulu and Miri. This study is focusing on how the public coping with subsidies reduction and their ways on how to adapt with their new standard of living as well as their alternatives in purchasing goods and services. General public has response positively to cope with subsidies reduction. Public reacts in subsidies reduction by coping with changes in spending and ways to cope. Apart from that, the public adapting to their new standard of living by buying only when necessary and do part time job. Due to subsidies reduction, the public alternatives are changing brand of product and buy Malaysian brand.